Integrasi Teknologi dalam Pembelajaran Biologi: Kajian Literatur terhadap Peran Kurikulum Berbasis Teknologi - Dini Zakiyatul Fitri Fitri; Fatiroh Fatiroh; Faizah Budi Rahayu; Diva Agustiani Agustiani; Indah Rahayu Rahayu; Kayla Berta Maulina Maulina; Usman Usman (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study aims to analyze the implementation of a technology-based curriculum in biology education, as well as to evaluate its impacts, challenges, and the role of teachers in the process. A descriptive qualitative method was employed through a literature review of 8 accredited journals and conference proceedings published within the last 5 years. The results indicate that technologies such as Learning Management Systems (LMS), interactive media, augmented reality, virtual laboratories, and artificial intelligence (AI) are effective in enhancing students’ understanding of abstract biological concepts, motivation to learn, and 21st-century skills. Teachers play crucial roles as facilitators, motivators, innovators, and character builders in integrating technology into teaching. However, challenges such as limited infrastructure and insufficient teacher training remain significant obstacles. The contribution of this study lies in its structured mapping of technology-based curriculum practices in biology learning, along with concrete recommendations for educational practitioners. The findings have implications for the development of policies and strategies to improve the quality of digital-based biology education sustainably.